Quasi-static puncture shear loading characteristics of GLARE/nanoclay laminates with various indenters - Thiyagu Murgaiyan; Vasudevan Alagumalai; Yoganandam Krishnamoorthy; Prem kumar; Arumugaprabu Veerasimman; Sundarakannan Rajendran; Megavannan Mani; Senthilkumar Jadamuni; Vigneshwaran Shanmugam; Oisik Das (Forces in Mechanics)
The potential challenge of delamination in fibre–metal laminates highlight the importance of improving interfacial bonding within the laminate. Developing a comprehensive understanding of the nature of this failure is essential for implementing effective mitigation strategies. This study explores fibre metal laminates comprising aluminium sheets and glass/epoxy, with and without the addition of nanoclay at varying weight percentages (0.5, 1, 1.5, and 2 wt.%). Fabrication involved the hand layup method followed by compression moulding, and the laminates were subjected to flexural, inter-laminar shear strength, and quasi-static punch shear tests (QS-PS). Two different indenters, flat and hemispheric, were employed in the QS-PS. Observations from flexural and interlaminar shear strength tests indicated that fibre metal laminate (FML) composites lacking nanoclay exhibit weakened interfacial bonding between aluminium and fibre layers. Notably, at 1.5 wt.% nanoclay, a substantial improvement in interfacial bonding between the fibre and aluminium layers improved the flexural strength (ca. 337 MPa), interfacial shear strength (ca. 16 MPa) and puncture resistance. The puncture failure modes exhibited variability based on the type of the indenter used, whether flat or hemispherical. For FML composites containing 2 wt.% nanoclay, the puncture shear strength differed significantly between the two indenters, measuring approximately 81 MPa under the flat indenter and about 49 MPa under the hemispherical indenter. Additionally, the corresponding energy absorption values were 880 KJ/g and 919 KJ/g for the flat and hemispherical indenters, respectively.